EUROPEAN EXPERIENCE OF EDUCATION IN YOUTH ORGANIZATIONS - Holovchuk, Svitlana Y. (Educological discourse, 2015)
Thearticlediscussestheeducationalaspectofyouthorganizationsasanimportantinstitutionfortheorganizationandfunctioningoftheeducationalsystem, someyouthsocialforcesthatareawareoftheirspecificity, particularlyinterestingplaceandroleinsociety. Objectivesoftheworkistoconduct IPO socio-political, educational, culturalandeducationalworkamongtheyouthparticipationinnationalyouthprogramsbothabroadandinUkraine.